The Effect of Turbo Cyclone Installation on 4 Stroke Motor Cycle on Fuel Consumption and Exhaust Emissions - Syahrul Huda; Wawan Purwanto; Budi Utomo Wisesa; Athaya Atsiq (MOTIVECTION : Journal of Mechanical, Electrical and Industrial Engineering, 2021)
This research examines the effect of installing a Turbo Cyclone on a 4 stroke gasoline engine on fuel consumption and exhaust emissions. This research is a quantitative study using experimental research methods. The 4 stroke petrol engine used is the Yamaha Jupiter MX 135 cc. The data were processed in several stages of analysis using the mean formula, fuel consumption, the percentage formula, and comparing the results of data analysis from each treatment. From the results of data analysis, it was found that the installation of the Turbo Cyclone had an effect on fuel consumption and exhaust emissions from the 4 stroke engine. The best effect is obtained from the installation of the Turbo Cyclone after the carburetor, fuel consumption shows a decrease of up to 8%, exhaust emissions show a decrease in HC levels by 9% and an increase in CO2 levels by 1%. Penelitian ini mambahas pengaruh pemasangan Turbo Cyclone pada mesin bensin 4 Tak terhadap konsumsi bahan bakar dan emisi gas buang. Penelitian ini merupakan penelitian kuantitatif dengan metode penelitian eksperimen. Mesin bensin 4 Tak yang digunakan adalah Yamaha Jupiter MX 135 cc. Data diolah dengan beberapa tahapan analisis menggunakan rumus mean, konsumsi bahan bakar, rumus persentase, dan membandingkan hasil analisis data dari masing-masing perlakuan. Dari hasil analisis data didapatkan adanya pengaruh dari pemasangan Turbo Cyclone terhadap konsumsi bahan bakar dan emisi gas buang dari mesin 4 Tak tersebut. Pengaruh yang paling baik didapat dari pemasangan Turbo Cyclone setelah karburator, konsumsi bahan bakar menunjukkan penurunan mencapai 8%, emisi gas buang menunjukkan penurunaan kadar HC sebesar 9% dan peningkatan kadar CO2 sebesar 1%.